2022
DOI: 10.3390/ijms23126648
|View full text |Cite
|
Sign up to set email alerts
|

Killing Two Birds with One Stone: Potential Therapies Targeting Psoriasis and Atherosclerosis at the Same Time

Abstract: Psoriasis is a chronic systemic inflammatory disease. Due to systemic inflammation, it is associated with many comorbidities. Among them, cardiovascular diseases represent the most common causes of morbidity and mortality in this population. Therefore, physicians treating patients with psoriasis should keep in mind that, as important as the treatment of psoriasis, awareness of cardiovascular risk deserves additional attention. Thus, in parallel with psoriasis treatment, a cardiovascular risk assessment must al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…As regular moderate-to-vigorous PE has essential anti-inflammatory and antioxidative abilities, a significant question is what dose of PE and intensity is needed to reduce the risk of psoriasis. Evidence has long demonstrated that patients with psoriasis take up less intensive PA than those without psoriasis [ 4 , 75 ] and have a higher risk of developing cardiovascular disease, obesity, and metabolic alteration, among others [ 86 ]. In recent years, two reviews and meta-analyses have quantified the association of psoriasis with PA [ 4 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…As regular moderate-to-vigorous PE has essential anti-inflammatory and antioxidative abilities, a significant question is what dose of PE and intensity is needed to reduce the risk of psoriasis. Evidence has long demonstrated that patients with psoriasis take up less intensive PA than those without psoriasis [ 4 , 75 ] and have a higher risk of developing cardiovascular disease, obesity, and metabolic alteration, among others [ 86 ]. In recent years, two reviews and meta-analyses have quantified the association of psoriasis with PA [ 4 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mercel Šabović et al [ 11 ], in a review article, present the common pathophysiological mechanisms of the psoriasis and cardiometabolic disorders and the atherosclerotic impact of some psoriasis treatments. The authors point out future perspectives in the treatment of psoriasis that should be accompanied by medications that target psoriasis-driven atherosclerosis.…”
mentioning
confidence: 99%